2021
DOI: 10.1073/pnas.2024846118
|View full text |Cite
|
Sign up to set email alerts
|

Substrate discrimination and quality control require each catalytic activity of TRAMP and the nuclear RNA exosome

Abstract: Quality control requires discrimination between functional and aberrant species to selectively target aberrant substrates for destruction. Nuclear RNA quality control in Saccharomyces cerevisiae includes the TRAMP complex that marks RNA for decay via polyadenylation followed by helicase-dependent 3′ to 5′ degradation by the RNA exosome. Using reconstitution biochemistry, we show that polyadenylation and helicase activities of TRAMP cooperate with processive and distributive exoribonuclease activities of the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Mtr4 is recruited to the exosome by Rrp47 and directly interacts with Rrp47 and binding partner Rrp6 at the exosome (64). Mtr4 adenylation activity also competes with Rrp6 deadenylation activity to determine how, depending on transcript stability, RNAs are processed or degraded (43). These connections to Rrp6 could impact Rrp6 function, core exosome function, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mtr4 is recruited to the exosome by Rrp47 and directly interacts with Rrp47 and binding partner Rrp6 at the exosome (64). Mtr4 adenylation activity also competes with Rrp6 deadenylation activity to determine how, depending on transcript stability, RNAs are processed or degraded (43). These connections to Rrp6 could impact Rrp6 function, core exosome function, or both.…”
Section: Discussionmentioning
confidence: 99%
“…We also overexpressed genes encoding members of the nuclear TRAMP complex: Trf4, Trf5, Air1, Air2, and Mtr4. The TRAMP complex is responsible for polyadenylation of transcripts targeted for degradation by the RNA exosome (42,43). We also overexpressed cytoplasmic RNA exosome cofactors Dom34 and Hbs1, which comprise the Dom34-Hbs1 ribosome dissociation complex that releases stalled ribosomes from aberrantly processed mRNAs (44)(45)(46).…”
Section: Specific Rna Exosome Cofactors Suppress the Growth Defect Of...mentioning
confidence: 99%
“…TRAMP allegedly targets anomalous or less steady tRNA by polyadenylating the 3′ end to furnish a single-stranded RNA extension that is long enough to facilitate the engagement of the Mtr4 helicase 35 . Das et al 36 found that exoribonuclease activities of Rrp6-associated RNA exosomes protected unfluctuating RNAs from TRAMP-mediated polyadenylation and degradation, whereas the catalytic activity of the exosome-TRAMP complex contributed to substrate distinction and degradation of less steady RNAs.…”
Section: Ribosome Quality Control Systemmentioning
confidence: 99%
“…Further catalytic activity is provided to the exosome by the RNase D-like 3 0 -5 0 exoribonuclease yRrp6/hEXOSC10 and its cofactors yRrp47/hC1D and yMpp6/hMPP6 (Briggs et al, 1998;Falk et al, 2017;Milligan et al, 2008;Mitchell et al, 2003;Schilders et al, 2007;Schuch et al, 2014;Wasmuth et al, 2014Wasmuth et al, , 2017Weick et al, 2018). yRrp6/hEXOSC10 possess distributive 3 0 -5 0 exoribonucleolytic activity employed to degrade substrates that do not pass through the channel of the complex (Das et al, 2021;Januszyk et al, 2011;Makino et al, 2015).…”
Section: The Rna Exosomementioning
confidence: 99%